Peran Guru Pendidikan Agama Islam Sebagai Fasilitator Dalam Pembelajaran Aqidah Akhlak Di Madrsah Tsanawiah - Armenia Muwardi, Diyah; Mulyanto; Faridatul Ulfa, Yetty (Universitas Majalengka, 2023)
The aim of this research is to determine the role of Islamic Religious Education teachers as facilitators in learning Aqidah Akhlak and to find out what factors support and inhibit the role of Islamic Religious Education teachers as facilitators in learning Aqidah Akhlak. The type of research used is field research. Research data collection techniques through observation, interviews and documentation. The results of the research show that the role of the teacher has been carried out well, the roles carried out include: As an educator and teacher by teaching science, providing examples, familiarizing and providing motivation. Teachers are also members of society by becoming good leaders and role models for society, becoming agents of reform for society. Teachers as administrators provide direction, initiative and assessment in education, enforce discipline and pass on a good culture to students. Teachers act as learning managers by maintaining the classroom environment, providing guidance, using time efficiently and effectively in achieving the goals of learning activities.